The Impact of a Revised National Childhood Immunization Schedule on Vaccination Defaulters - Ngiap Chuan Tan; Jeremy Pang; Eileen Koh (Vaccines, 2023)
Immunization schedules affect community vaccine uptake rates, especially in children who have defaulted on their regular immunization timelines. In 2020, Singapore revised its National Childhood Immunization Schedule (NCIS) to incorporate two new combination vaccines: the hexavalent hepatitis, diphtheria, acellular pertussis, tetanus (DTaP), hemophilus influenzae b (Hib), inactivated poliovirus (IPV) (6-in-1), and the quadrivalent measles, mumps, rubella, and varicella (MMRV) vaccines, thus reducing the mean number of clinic visits and vaccine doses by two. Our database study aims to evaluate the impact of the 2020 NCIS on catch-up vaccination uptake rates in children at 18 and 24 months of age and the catch-up immunization rates of individual vaccines at two years. Vaccination data from two cohorts, in 2018 (n = 11,371) and in 2019 (n = 11,719), were extracted from the Electronic Medical Records. Catch-up vaccination rates increased by 5.2% and 2.6% in children on the new NCIS at 18 and 24 months, respectively. The uptake of individual 5-in-1 (DTaP, IPV, Hib), MMR, and pneumococcal vaccines increased by 3.7%, 4.1%, and 1.9% at 18 months. Reduced vaccination doses and visits in the new NCIS bring direct and indirect benefits to parents and promote vaccination adherence for their children. These findings highlight the importance of timelines in improving catch-up vaccination rates in any NCIS.